DEVELOPMENT OF THE BIOGAS INDUSTRY AND PROSPECTS FOR THE IMPLEMENTATION OF BIOGAS PLANTS IN KAZAKHSTAN - Abilmazhinov, E.T.; Akimzhanov, A.Zh.; Shaiakhmetov, E.Y.; Anibaev, S.N.; Nurgaliyev, N.N.; Shakerkhan, K.O.; Sailauov, D.M. (KU Publ., 2021)
The article provides an overview of biogas technologies abroad and in Kazakhstan, the experience of foreign countries in the biogas industry, the development and prospects for the introduction of biogas plants in the Republic of Kazakhstan for the environmentally friendly and profitable processing of organic agricultural waste, food production, processing enterprises. Recommendations are given on the specifics of the design of biogas plants in the difficult climatic conditions of Kazakhstan (especially in the north, east and central Kazakhstan). The current design of a biogas plant (filling volume 3.7 m3) is shown, in the design of which units of our own design were used, this is a peristaltic pump and a raw material grinder. The efficiency of a number of units, in particular a new design peristaltic pump, was shown in the course of the experiments.
Keywords: renewable energy sources; biomass; biogas; biogas plant; biofertilizer